Analisis In Silico Filogenetik Coffea sp. Berdasarkan Gen matK dan rbcL: Dasar Pemuliaan Profil Sensorik - Firnanda Ayu Rizki; Isnawati (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to analyze phylogenetic relationships, genetic distances, and the potential for successful hybridization based on concatenated matK and rbcL sequences. The study was conducted in silico on 11 coffee species obtained from the NCBI GenBank database. Sequence data were analyzed using bioinformatics tools for alignment, concatenated sequences, phylogenetic reconstruction, and genetic distance calculation. Phylogenetics produced a stable and accurate topology. Species showed three categories of hybridization compatibility based on genetic distance values; high ensured gene introgression stability, moderate produced heterotic hybrids, and low risked incompatibility and genetic barriers. The study concluded that species with low genetic distance and close kinship have the potential for successful hybridization. The integration of phylogenetics and genetic distance based on matK and rbcL sequences proved effective in mapping interspecies compatibility oriented towards sensory profile development. These findings provide a strategic foundation for the efficiency of modern coffee breeding programs with superior taste and aroma characteristics.